COMPOSITION: INSPIRATION OR TECHNIQUE? (A CRITIQUE ON THE MUSICAL COMPOSITION SYSTEMS) - Vangelis KARAFILLIDIS (Studia Universitatis Babeş-Bolyai. Musica)
Musical composition systems play the role of a scientific-like approach to composition. Under this perspective one can study harmony, counterpoint, fugue, music morphology, serial composition techniques, etc. and utilize this knowledge in order to compose music. What is the influence between musical composition systems and inspiration? How these two contradicted procedures can be combined and give a balanced result? This article is trying to focus on these questions, to analyze the evolution of the musical composition systems and to survey the significance of inspiration in musical composition.